Method for producing toner for developing electrostatic images, and toner for developing electrostatic images
A two-step agglomeration method for toner production using amorphous resin particles with controlled diameters and glass transition temperatures achieves a narrow particle size distribution, enhancing chargeability and image quality by stabilizing granulation.
Patent Information
- Application Number
- JP2021055130
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-03-29
AI Technical Summary
Existing methods for producing toner for developing electrostatic images struggle with achieving a narrow particle size distribution, particularly when using core-shell structures, leading to unstable agglomeration and broad particle size distributions.
A method involving a two-step agglomeration process where first and second amorphous resin particles with specific volume average particle diameters and glass transition temperatures are aggregated and fused to form toner particles, with the second amorphous resin particles having a smaller diameter and a glass transition temperature between 50°C and 63°C, ensuring controlled agglomeration and fusion.
This approach results in toner particles with a narrower particle size distribution, improving chargeability and image quality by stabilizing granulation properties and preventing exposure of unstable core materials on the surface.
Smart Images

Figure 0007613206000003 
Figure 0007613206000004 
Figure 0007613206000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a toner for developing electrostatic images, and a toner for developing electrostatic images. [Background technology]
[0002] For example, Patent Document 1 discloses "a toner for developing electrostatic images, comprising core particles containing a binder resin and a colorant, and a shell layer covering the core particles, wherein the binder resin contains at least one of a crystalline polyester resin and an amorphous resin, and the shell layer contains amorphous resin fine particles, the amorphous resin fine particles having a volume average particle size of 20 to 800 nm and a glass transition temperature of 65° C. or higher, and the content of the amorphous resin fine particles is in the range of 5 to 25% by weight based on the weight of the core particles."
[0003] Patent Document 2 also discloses a method for producing a toner for developing electrostatic images, which comprises toner particles having a core-shell structure in which a shell layer made of a shell resin containing a polyester resin is formed on the surface of core particles containing a base resin, the method comprising: a phase inversion emulsification step of adding an aqueous medium to a shell resin solution obtained by dissolving a shell resin in a hydrophilic organic solvent to obtain an emulsion in which oil droplets made of the shell resin solution are dispersed in the aqueous medium, and removing the organic solvent from the oil droplets to obtain shell resin fine particles; and a shell layer formation step of adding the shell resin fine particles obtained in the phase inversion emulsification step to the aqueous medium in which core particles are dispersed, and aggregating and fusing the shell resin fine particles to the surfaces of the core particles, the acid value of the shell resin being 15 to 30 mgKOH / g, the removal of the organic solvent in the phase inversion emulsification step being performed at a temperature not lower than the glass transition point of the shell resin and not higher than the glass transition point of the shell resin +30° C., and the particle size distribution (CV value) of the shell resin fine particles being 10 to 35%.
[0004] Furthermore, Patent Document 3 discloses a method for producing functional particles, comprising: "passing a mixed slurry containing core particles, which are resin particles, and shell particles, which are resin particles or inorganic particles having a volume average particle diameter smaller than that of the core particles, through a coiled pipe while heating the mixed slurry to a temperature equal to or higher than the glass transition point of the core particles, thereby obtaining functional particles in which the shell particles are attached to the surfaces of the core particles." [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-3840 A [Patent Document 2] JP 2014-2310 A [Patent Document 3] JP 2008-65180 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has an object to provide a method for producing a toner for developing electrostatic images, the method including: a first aggregation step of aggregating at least the first amorphous resin particles in a dispersion containing first amorphous resin particles; a second aggregation step of aggregating second amorphous resin particles to the first aggregated particles in a dispersion containing first aggregated particles formed by aggregating the first amorphous resin particles and second amorphous resin particles; and a fusion-coalescence step of heating a dispersion containing second aggregated particles formed by aggregating the second amorphous resin particles to the first aggregated particles to form toner particles by fusing and coalescing the second aggregated particles. The object of the present invention is to provide a method for producing a toner for developing electrostatic images, the toner having a narrow particle size distribution compared to a case in which the volume average particle size DA of the first amorphous resin particles is larger than the volume average particle size DB of the second amorphous resin particles, or the glass transition temperatures of the first amorphous resin particles and the second amorphous resin particles are less than 50° C. or the glass transition temperature of the second amorphous resin particles is more than 63° C. [Means for solving the problem]
[0007] Specific means for solving the above problems include the following aspects. <1> a first aggregation step of aggregating at least the first amorphous resin particles in a dispersion liquid containing the first amorphous resin particles; a second aggregation step of aggregating the second amorphous resin particles to the first aggregated particles in a dispersion liquid containing first aggregated particles formed by aggregating the first amorphous resin particles and second amorphous resin particles; a fusion / coalescence process of heating a dispersion liquid containing second aggregated particles in which the second amorphous resin particles are aggregated to the first aggregated particles, thereby fusing and coalescing the second aggregated particles to form toner particles; having a volume average particle diameter DB of the second amorphous resin particles is smaller than a volume average particle diameter DA of the first amorphous resin particles; The first amorphous resin particles have a glass transition temperature of 50° C. or higher, and the second amorphous resin particles have a glass transition temperature of 50° C. or higher and 63° C. or lower. A method for producing a toner for developing electrostatic images. <2> The second aggregation step is carried out multiple times, and at least one of the second aggregation steps, except for the last second aggregation step, of the plurality of second aggregation steps, disperses the first aggregated particles into the second amorphous resin particles in a dispersion liquid containing the first aggregated particles, the second amorphous resin particles, and release agent particles. Amorphous A step of aggregating the release agent particles together with the resin particles. <1> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <3> The exposed ratio of the release agent on the surface of the resulting toner particles is 25% or less. <2> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <4> The difference (DA-DB) between the volume average particle diameter DA of the first amorphous resin particles and the volume average particle diameter DB of the second amorphous resin particles is 20 nm or more. <1> ~ <3> 13. The method for producing the toner for developing electrostatic images according to claim 12. <5> The difference (DA-DB) between the volume average particle diameter DA of the first amorphous resin particles and the volume average particle diameter DB of the second amorphous resin particles is 20 nm or more and 300 nm or less. <4> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <6> The first amorphous resin particles have a volume average particle size DA of 100 nm or more and 300 nm or less, The second amorphous resin particles have a volume average particle diameter DB of 20 nm or more and 170 nm or less. <1> ~ <5> 13. The method for producing the toner for developing electrostatic images according to claim 12. <7> the second amorphous resin particles include two or more types of amorphous resin particles having different volume average particle diameters, The volume average particle size of the mixed particles obtained by mixing the two or more kinds of amorphous resin particles having different volume average particle sizes is in the range of 20 nm to 170 nm, which is the range of the volume average particle size DB of the second amorphous resin particles. <6> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <8> In the particle size distribution of the second amorphous resin particles, the ratio of particles having a particle size of 100 nm or less is 10% by volume or more and 100% by volume or less. <1> ~ <7> 13. The method for producing the toner for developing electrostatic images according to claim 12. <9> <1> ~ <8> 2. A toner for developing electrostatic images, comprising toner particles obtained by the method for producing a toner for developing electrostatic images according to claim 1. Effect of the Invention
[0008] <1> According to the invention related to the above, there is provided a method for producing a toner for developing electrostatic images, the method including: a first aggregation step of aggregating at least the first amorphous resin particles in a dispersion containing the first amorphous resin particles; a second aggregation step of aggregating second amorphous resin particles to the first aggregated particles in a dispersion containing first aggregated particles formed by aggregating the first amorphous resin particles and second amorphous resin particles; and a fusion-coalescence step of heating a dispersion containing second aggregated particles formed by aggregating the second amorphous resin particles to the first aggregated particles to fuse and coalesce the second aggregated particles to form toner particles. The method provides a toner for developing electrostatic images, the particle size distribution of which is narrower than that of a case in which the volume average particle size DA of the first amorphous resin particles is larger than the volume average particle size DB of the second amorphous resin particles, or the glass transition temperatures of the first amorphous resin particles and the second amorphous resin particles are less than 50° C. or the glass transition temperature of the second amorphous resin particles is more than 63° C.
[0009] <2> or <3> According to the invention, there is provided a method for producing a toner for developing electrostatic images, which has a narrower particle size distribution even when release agent particles are used to form the second aggregate particles, compared to a case in which the volume average particle size DA of the first amorphous resin particles is smaller than the volume average particle size DB of the second amorphous resin particles, or the glass transition temperatures of the first and second amorphous resin particles are less than 50°C, or the glass transition temperature of the second amorphous resin particles is more than 63°C.
[0010] <4> or <5> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which has a narrower particle size distribution than when the difference (DA-DB) between the volume average particle size DA of the first amorphous resin particles and the volume average particle size DB of the second amorphous resin particles is less than 20 nm.
[0011] <6> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which has a narrower particle size distribution than when the first amorphous resin particles have a volume average particle size DA of less than 100 nm or the second amorphous resin particles have a volume average particle size DB of more than 170 nm.
[0012] <7> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which has a narrower particle size distribution than when the volume average particle size of the mixed particles obtained by mixing two or more types of amorphous resin particles having different volume average particle sizes as second amorphous resin particles exceeds 170 nm.
[0013] <8> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, in which the particle size distribution of the second amorphous resin particles is narrower than when the proportion of particles having a particle size of 100 nm or less is less than 10 volume %.
[0014] <9> According to the invention related to the above, there is provided a method for producing a toner for developing electrostatic images, the method including: a first aggregation step of aggregating at least the first amorphous resin particles in a dispersion containing first amorphous resin particles; a second aggregation step of aggregating second amorphous resin particles to the first aggregate particles in a dispersion containing first aggregate particles formed by aggregating the first amorphous resin particles and second amorphous resin particles; and a fusion-coalescence step of heating a dispersion containing second aggregate particles formed by aggregating the second amorphous resin particles to the first aggregate particles to fuse and coalesce the second aggregate particles to form toner particles. In this method, a toner for developing electrostatic images having a narrow particle size distribution is provided, as compared to a toner produced by a method for producing a toner for developing electrostatic images in which the volume average particle size DA of the first amorphous resin particles is larger than the volume average particle size DB of the second amorphous resin particles, or in which the glass transition temperatures of the first amorphous resin particles and the second amorphous resin particles are less than 50° C., or the glass transition temperature of the second amorphous resin particles is more than 63° C. [Brief description of the drawings]
[0015] [Figure 1] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a process cartridge according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described as an example. These descriptions and examples are for illustrating the present invention, but are not intended to limit the present invention.
[0017] In this specification, a numerical range indicated using "~" indicates a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.
[0018] In this specification, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes, so long as the intended purpose of the process is achieved.
[0019] When an embodiment is described with reference to the drawings in this specification, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this.
[0020] In the present specification, each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified.
[0021] In this specification, the "toner for developing electrostatic images" is also simply referred to as "toner".
[0022] <Method of manufacturing toner for developing electrostatic images> The toner manufacturing method according to the present embodiment includes a first aggregation step of aggregating at least the first amorphous resin particles in a dispersion liquid containing the first amorphous resin particles; a second aggregation step of aggregating the second amorphous resin particles to the first aggregated particles in a dispersion liquid containing first aggregated particles formed by aggregating the first amorphous resin particles and second amorphous resin particles; a fusion / coalescence process of heating a dispersion liquid containing second aggregated particles in which the first aggregated particles and the second amorphous resin particles are aggregated to form toner particles by fusing and coalescing the second aggregated particles; has. The volume average particle diameter DB of the second amorphous resin particles is smaller than the volume average particle diameter DA of the first amorphous resin particles. The first amorphous resin particles have a glass transition temperature of 50° C. or higher, and the second amorphous resin particles have a glass transition temperature of 50° C. or higher and 63° C. or lower.
[0023] Here, the toner particles obtained by the toner manufacturing method according to this embodiment are toner particles having a core portion (hereinafter also referred to as a core portion) and a coating layer (hereinafter also referred to as a shell layer) that coats the core portion (hereinafter also referred to as a core / shell toner particles). The core portion corresponds to a site where the first aggregated particles formed by aggregation of the first amorphous resin particles are fused and coalesced, and corresponds to a site where the second amorphous resin particles aggregated to the first aggregated particles are fused and coalesced.
[0024] The toner manufacturing method according to the present embodiment produces a toner having a narrow particle size distribution, the reason for which is presumed to be as follows.
[0025] A method for producing toner particles by emulsion aggregation is known. However, in recent years, there has been a demand for precise control of the structure of toner particles, and even in the emulsion aggregation method, there has been a demand for further improvement in the granulation stability of toner particles. In particular, there is a demand for improving granulation stability and further narrowing the particle size distribution when producing core / shell toner particles by emulsion aggregation, because the particle size distribution of toner particles affects the charging properties of the toner, and further narrowing the particle size distribution of toner particles leads to improved image quality and quality.
[0026] Therefore, in the toner manufacturing method according to this embodiment, the volume average particle diameter DB of the second amorphous resin particles for forming the shell layer is made smaller than the volume average particle diameter DA of the first amorphous resin particles for forming the core portion. As a result, the second amorphous resin particles, which have a large specific surface area, i.e., a large surface energy, tend to melt before the first amorphous resin particles. Also, the contact area between the second amorphous resin particles and the first aggregated particles (i.e., the cores after fusion and coalescence) increases, and the cohesive force of the second amorphous resin particles is strengthened. As a result, it is believed that from the second aggregation process to the fusion and coalescence process, the core material, which has unstable aggregation controllability, is prevented from being exposed to the outermost surface of the aggregate (i.e., the outside of the second amorphous resin particles that constitute the shell layer), thereby stabilizing the granulation property. Therefore, the particle size distribution of the toner particles is narrowed.
[0027] The first amorphous resin particles have a glass transition temperature of 50° C. or higher, and the second amorphous resin particles have a glass transition temperature of 50° C. or higher and 63° C. or lower. By setting the glass transition temperature of the second amorphous resin particles to 50°C or more and 63°C or less, and setting the volume average particle diameter DB of the second amorphous resin particles smaller than the volume average particle diameter DA of the first amorphous resin particles, the second amorphous resin particles tend to melt before the core material encapsulated in the first aggregates of the first amorphous resin particles in the first aggregation step. As a result, it is considered that the core material, which has unstable aggregation controllability, is prevented from being exposed to the shell layer surface from the second aggregation step to the fusion and coalescence step, and granulation property is stabilized. This narrows the particle size distribution of the toner particles.
[0028] In addition, in the range where the glass transition temperature of the first amorphous resin particles is less than 50°C or the glass transition temperature of the second amorphous resin particles is more than 63°C, when the difference between the volume average particle diameter DA of the first amorphous resin particles and the volume average particle diameter DB of the second amorphous resin particles is small, the particle size distribution is deteriorated. This is because the first amorphous resin particles constituting the core part tend to melt earlier than the second amorphous resin particles constituting the shell layer, and the material of the core part with unstable aggregation controllability is exposed to the shell layer surface from the second aggregation step to the fusion and coalescence step, so that some particles reaggregate and become coarse from the second aggregation step to the fusion and coalescence step, and the granulation property is deteriorated. When the glass transition temperature of the second amorphous resin particles is less than 50°C, the deterioration of the particle size distribution is aggravated in the external addition step. This is because the toner particles reaggregate and become coarse due to the heat during external addition.
[0029] From the above, it is presumed that the toner manufacturing method according to this embodiment produces toner with a narrow particle size distribution.
[0030] In the toner manufacturing method according to this embodiment, the first amorphous resin particles have a glass transition temperature of 50° C. or higher, and the second amorphous resin particles have a glass transition temperature Tg of 50° C. or higher and 63° C. or lower, but from the viewpoint of narrowing the particle size distribution of the toner particles, it is preferable that the first amorphous resin particles have a glass transition temperature of 50° C. or higher and that the second amorphous resin particles have a glass transition temperature of 50° C. or higher and 60° C. or lower. From the viewpoint of low-temperature fixability, it is preferable that the first amorphous resin particles have a glass transition temperature of 63° C. or lower. The glass transition temperature of the resin particles is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in JIS K 7121-1987 "Method for measuring glass transition temperature of plastics."
[0031] From the viewpoint of narrowing the particle size distribution of the toner particles, the difference (DA-DB) between the volume average particle size DA of the first amorphous resin particles and the volume average particle size DB of the second amorphous resin particles is preferably 20 nm or more, more preferably 30 nm or more, and even more preferably 45 nm or more. However, from the viewpoint of manufacturability (that is, controllability of the toner particle size and particle size distribution), the difference (DA-DB) is preferably 300 nm or less, and more preferably 270 nm or less.
[0032] The volume average particle diameter DA of the first amorphous resin particles is preferably 100 nm or more and 300 nm or less, more preferably 120 nm or more and 280 nm or less, and even more preferably 140 nm or more and 260 nm or less, from the viewpoint of narrowing the particle size distribution of the toner particles.
[0033] Here, the first amorphous resin particles may contain two or more types of amorphous resin particles having different volume average particle sizes. However, the volume average particle diameter of each of the two or more types of amorphous resin particles as the first amorphous resin particles may be outside the range of the volume average particle diameter DA of the above-mentioned first amorphous resin particles, but from the viewpoint of narrowing the particle size distribution of the toner particles, it is preferable that the volume average particle diameter of the mixed particles after mixing two or more types of amorphous resin particles having different volume average particle diameters is within the range of the volume average particle diameter DA of the above-mentioned first amorphous resin particles.
[0034] The volume average particle diameter DB of the second amorphous resin particles is preferably 20 nm or more and 170 nm or less, more preferably 40 nm or more and 150 nm or less, and even more preferably 50 nm or more and 130 nm or less, from the viewpoint of narrowing the particle size distribution of the toner particles.
[0035] Here, the second amorphous resin particles may contain two or more types of amorphous resin particles having different volume average particle sizes. However, the volume average particle diameter of each of the two or more types of amorphous resin particles as the second amorphous resin particles may be outside the range of the volume average particle diameter DB of the second amorphous resin particles. However, from the viewpoint of narrowing the particle size distribution of the toner particles, it is preferable that the volume average particle diameter of the mixed particles after mixing two or more types of amorphous resin particles having different volume average particle diameters is within the range of the volume average particle diameter DB of the second amorphous resin particles. The same applies to the ratio of particles having a numerical particle diameter D16p and a particle diameter of 100 nm or less in the second amorphous resin particles described below.
[0036] The number particle diameter D16p of the second amorphous resin particles is preferably 5 nm or more and 140 nm or less, and more preferably 10 nm or more and 100 nm or less, from the viewpoint of narrowing the particle size distribution of the toner particles.
[0037] In the particle size distribution of the second amorphous resin particles, the ratio of particles having a particle size of 100 nm or less is preferably 10 vol% or more and 100 vol% or less, more preferably 15 vol% or more and 100 vol% or less, and even more preferably 20 vol% or more and 100 vol% or less. In the particle size distribution of the second amorphous resin particles, when the ratio of particles with a particle size of 100 nm or less is within the above range, the ratio of fine particles increases, and the second amorphous resin particles, which have a large specific surface area, i.e., a large surface energy, tend to melt before the first amorphous resin particles. In addition, the contact area of the second amorphous resin particles with the first aggregated particles (i.e., the core portion after fusion and coalescence) increases, thereby strengthening the aggregation force of the second amorphous resin particles. As a result, in the second aggregation step to the fusion and coalescence step, the material of the core portion, which has unstable aggregation controllability, is prevented from being exposed to the outermost surface of the aggregate (the outside of the second amorphous resin particles that constitute the shell layer), and it is considered that the granulation property is stabilized. Therefore, the particle size distribution of the toner particles can be narrowed.
[0038] The particle size distribution and particle size of the resin particles are measured as follows. The particle size distribution is obtained by measurement with a laser diffraction particle size distribution analyzer (for example, LA-700 manufactured by Horiba, Ltd.). Based on the measured particle size distribution, cumulative distributions of volume and number are drawn for each particle size range (channel) divided from the small diameter side, and the particle size at 16% of the cumulative size is defined as the volume particle size D16v, the number particle size D16p, the particle size at 50% of the cumulative size as the volume average particle size D50v, the cumulative number average particle size D50p, and the particle size at 84% of the cumulative size as the volume particle size D84v and the number particle size D84p. Using these, the volumetric particle size distribution index (GSDv) is (D84v / D16v) 1 / 2 The number size distribution index (GSDp) is (D84p / D16p) 1 / 2 It is calculated as: The ratio of particles with a particle size of 100 nm or less is determined by accumulating the frequency of particles counted in the particle size range (channel) of 0 to 100 nm among the particles measured and detected.
[0039] In the toner manufacturing method according to the present embodiment, the second aggregation step may be performed a plurality of times. Among the plurality of second aggregation steps, at least one of the second aggregation steps, except for the last second aggregation step, comprises: a step of dispersing the first aggregate particles into the second amorphous resin particles in a dispersion liquid containing the first aggregate particles, the second amorphous resin particles, and release agent particles; Amorphous The step may also include agglomerating the release agent particles together with the resin particles.
[0040] As image quality continues to improve, precise control of toner structure is required to place the materials that make up the toner particles in positions suitable for their functionality. It is known that the release function can be efficiently achieved by placing the release agent, which is responsible for the release function from the fixing member, on the toner surface. However, when the release agent is disposed on the toner surface side (i.e., when the release agent is contained in the shell layer), the release agent may be exposed on the surface of the toner particles. Since the release agent has almost no functional groups, the release agent particles in the dispersion liquid are unstable. Therefore, in the emulsion aggregation method, during the temperature rise to the fusion and coalescence temperature of the aggregated particles, the release agent comes out and leaks out onto the aggregated particle surface, the repulsive force between the aggregated particles decreases, and two or more aggregated particles re-aggregate, which may cause the particle size distribution of the resulting toner particles to become wider.
[0041] In contrast, in the toner manufacturing method according to the present embodiment, even if release agent particles are used together with the second amorphous resin particles that form the shell layer, a toner having a narrow particle size distribution can be obtained. The reason for this is presumed to be as follows. First, by making the volume average particle diameter DB of the second amorphous resin particles for forming the shell layer smaller than the volume average particle diameter DA of the first amorphous resin particles for forming the core portion, the second amorphous resin particles, which have a large specific surface area, i.e., a large surface energy, tend to flow relatively earlier than the first amorphous resin particles, which makes it difficult for the release agent to appear on the surface of the aggregated particles during the temperature rise to the fusion and coalescence temperature of the aggregated particles. In addition, the smaller the diameter of the second amorphous resin particles, the more difficult it is for the release agent particles to physically appear on the aggregate particle surface, which is believed to be due to an increase in the contact area between the surface of the first aggregate particle (i.e., the core particle) and the second amorphous resin particles. From the above, it is presumed that in the toner manufacturing method according to this embodiment, even if release agent particles are used together with the second amorphous resin particles that form the shell layer, a toner having a narrow particle size distribution can be obtained.
[0042] In the toner manufacturing method according to the present embodiment, the exposure rate of the release agent on the surface of the obtained toner particles is preferably 25% or less, and more preferably 15% or less, from the viewpoint of narrowing the particle size distribution. The exposure rate of the release agent is ideally 0%.
[0043] The method for measuring the exposure rate of the release agent on the toner particle surface is as follows. The release agent exposure rate is measured by XPS (X-ray photoelectron spectroscopy) using toner particles as a measurement sample. The XPS measurement device used is a JPS-9000MX manufactured by JEOL Ltd., and the measurement is performed using MgKα radiation as the X-ray source, with the acceleration voltage set to 10 kV and the emission current set to 30 mA. Here, the amount of binder resin and the amount of release agent on the surface of the toner particles are quantified by the peak separation method of the C1s spectrum. In the peak separation method, the measured C1s spectrum is separated into each component using curve fitting by the least squares method. For the component spectrum that serves as the basis for the separation, the C1s spectrum obtained by measuring the release agent and binder resin used in the preparation of the toner particles separately is used. C1 derived from the binder resin and release agent on the surface of the toner particles S C1 due to the release agent on the surface of the toner particles versus spectral intensity S The ratio of the spectral intensities is calculated as the exposure rate (%) of the release agent on the toner particle surface.
[0044] Hereinafter, the toner manufacturing method according to the present embodiment will be described in detail.
[0045] In the toner production method according to the present embodiment, toner particles are produced through a first aggregation step, a fusion / coalescence step, and a second aggregation step. In the toner production method according to the present embodiment, after the toner particles are produced, an external additive may be added to the toner particles.
[0046] Each step will be described in detail below. In the following description, a method for obtaining toner particles containing an amorphous resin and a crystalline resin as binder resins, a colorant, and a release agent will be described, but the crystalline resin, the colorant, and the release agent are used as necessary. Of course, additives other than the colorant and the release agent may be used.
[0047] (Dispersion liquid preparation process) First, the steps of preparing various dispersion liquids will be described. First, in addition to each resin particle dispersion liquid (amorphous resin particle dispersion liquid and crystalline resin particle dispersion liquid) in which each resin particle that will become the binder resin is dispersed, for example, a colorant particle dispersion liquid in which colorant particles are dispersed and a release agent particle dispersion liquid in which release agent particles are dispersed are prepared.
[0048] -Resin particle dispersion- The resin particle dispersion liquid is prepared, for example, by dispersing resin particles in a dispersion medium with the aid of a surfactant.
[0049] The resin particles used are amorphous resin particles and crystalline resin particles. However, when amorphous resin particles and crystalline resin particles are used in combination, the mass ratio of the amorphous resin to the crystalline resin in the toner particles (crystalline resin / amorphous resin) is preferably from 3 / 97 to 50 / 50, and more preferably from 7 / 93 to 30 / 70.
[0050] Here, the term "amorphous resin" refers to a resin that, in a thermal analysis measurement using differential scanning calorimetry (DSC), has only a stepwise endothermic change rather than a clear endothermic peak, is a solid at room temperature, and is thermoplasticized at a temperature equal to or higher than the glass transition temperature. On the other hand, a crystalline resin refers to a resin that has a clear endothermic peak rather than a stepwise change in endothermic amount in differential scanning calorimetry (DSC). Specifically, for example, a crystalline resin means a resin whose half-width of an endothermic peak is within 10°C when measured at a heating rate of 10°C / min, and an amorphous resin means a resin whose half-width exceeds 10°C or a resin in which no clear endothermic peak is observed.
[0051] The amorphous resin constituting the amorphous resin particles will be described. Examples of the amorphous resin include known amorphous resins such as amorphous polyester resin, amorphous vinyl resin (e.g., styrene-acrylic resin, etc.), epoxy resin, polycarbonate resin, polyurethane resin, etc. Among these, amorphous polyester resin and amorphous vinyl resin (particularly styrene-acrylic resin) are preferred, and amorphous polyester resin is more preferred. In addition, it is also a preferred embodiment to use an amorphous polyester resin and a styrene-acrylic resin in combination as the amorphous resin. It is also a preferred embodiment to use an amorphous resin having an amorphous polyester resin segment and a styrene-acrylic resin segment as the amorphous resin. In particular, when an amorphous resin having an amorphous polyester resin segment and a styrene acrylic resin segment is used as the amorphous resin, in the case where the above resins are bonded by ester bonds, the resin is easily compatible with an ester-based release agent, and therefore has better toner melting properties. Therefore, even when an image with a large amount of toner is formed at high speed on a recording medium having unevenness, image voids are more suppressed.
[0052] Amorphous polyester resin The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. As the amorphous polyester resin, a commercially available product or a synthesized product may be used.
[0053] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferred as the polyvalent carboxylic acid. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0054] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, aromatic diols and alicyclic diols are preferred as polyhydric alcohols, and aromatic diols are more preferred. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0055] The amorphous polyester resin is obtained by a known manufacturing method. Specifically, for example, the polymerization temperature is set to 180°C or more and 230°C or less, the reaction system is depressurized as necessary, and the reaction is carried out while removing water and alcohol generated during condensation. If the raw material monomer is not dissolved or compatible at the reaction temperature, a high-boiling point solvent may be added as a dissolution aid to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the dissolution aid. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed with the monomer and then polycondensed with the main component.
[0056] The amorphous polyester resin may be a modified amorphous polyester resin in addition to an unmodified amorphous polyester resin. The modified amorphous polyester resin is an amorphous polyester resin having a bond group other than an ester bond, or an amorphous polyester resin having a resin component different from polyester bonded by a covalent bond or an ionic bond. The modified amorphous polyester resin may be, for example, a resin modified at the end by reacting an amorphous polyester resin having a functional group such as an isocyanate group introduced at the end with an active hydrogen compound.
[0057] The proportion of the amorphous polyester resin in the total binder resin is preferably 60% by mass or more and 98% by mass or less, more preferably 65% by mass or more and 95% by mass or less, and even more preferably 70% by mass or more and 90% by mass or less.
[0058] Styrene acrylic resin The styrene-acrylic resin is a copolymer obtained by copolymerizing at least a styrene-based monomer (a monomer having a styrene skeleton) and a (meth)acrylic-based monomer (a monomer having a (meth)acrylic group, preferably a monomer having a (meth)acryloxy group). The styrene-acrylic resin includes, for example, a copolymer of a styrene monomer and a (meth)acrylic acid ester monomer. The acrylic resin portion of the styrene-acrylic resin is a partial structure formed by polymerizing either an acrylic monomer or a methacrylic monomer, or both. In addition, the term "(meth)acrylic" includes both "acrylic" and "methacrylic".
[0059] Examples of the styrene monomer include styrene, α-methylstyrene, metachlorostyrene, parachlorostyrene, parafluorostyrene, paramethoxystyrene, meta-tert-butoxystyrene, para-tert-butoxystyrene, paravinylbenzoic acid, paramethyl-α-methylstyrene, etc. The styrene monomer may be used alone or in combination of two or more kinds.
[0060] Examples of the (meth)acrylic monomer include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, isobornyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, etc. The (meth)acrylic monomer may be used alone or in combination of two or more.
[0061] The polymerization ratio of the styrene-based monomer to the (meth)acrylic monomer is preferably styrene-based monomer:(meth)acrylic monomer=70:30 to 95:5 on a mass basis.
[0062] The styrene-acrylic resin may have a crosslinked structure. The styrene-acrylic resin having a crosslinked structure can be produced, for example, by copolymerizing a styrene-based monomer, a (meth)acrylic monomer, and a crosslinkable monomer. The crosslinkable monomer is not particularly limited, but is preferably a bifunctional or higher (meth)acrylate compound.
[0063] The method for producing the styrene-acrylic resin is not particularly limited, and for example, solution polymerization, precipitation polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. The polymerization reaction is carried out by a known operation (for example, a batch system, a semi-continuous system, a continuous system, etc.).
[0064] The proportion of the styrene-acrylic resin in the total binder resin is preferably from 0% to 20% by mass, more preferably from 1% to 15% by mass, and even more preferably from 2% to 10% by mass.
[0065] Amorphous resin having an amorphous polyester resin segment and a styrene-acrylic resin segment (hereinafter also referred to as "hybrid amorphous resin") The hybrid amorphous resin is an amorphous resin in which an amorphous polyester resin segment and a styrene-acrylic resin segment are chemically bonded to each other. Examples of the hybrid amorphous resin include a resin having a main chain made of a polyester resin and a side chain made of a styrene-acrylic resin chemically bonded to the main chain; a resin having a main chain made of a styrene-acrylic resin and a side chain made of a polyester resin chemically bonded to the main chain; a resin having a main chain formed by chemically bonding a polyester resin and a styrene-acrylic resin; a resin having a main chain formed by chemically bonding a polyester resin and a styrene-acrylic resin, and at least one of a side chain made of a polyester resin chemically bonded to the main chain and a side chain made of a styrene-acrylic resin chemically bonded to the main chain; and the like.
[0066] The amorphous polyester resin and the styrene-acrylic resin in each segment are as described above, and therefore the description will be omitted.
[0067] The total amount of the polyester resin segment and the styrene-acrylic resin segment in the entire hybrid amorphous resin is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and even more preferably 100 mass%.
[0068] In the hybrid amorphous resin, the proportion of the styrene-acrylic resin segment in the total amount of the polyester resin segment and the styrene-acrylic resin segment is preferably 20% by mass or more and 60% by mass or less, more preferably 25% by mass or more and 55% by mass or less, and even more preferably 30% by mass or more and 50% by mass or less.
[0069] The hybrid amorphous resin is preferably produced by any one of the following methods (i) to (iii). (i) After preparing a polyester resin segment by condensation polymerization of a polyhydric alcohol and a polycarboxylic acid, a monomer constituting a styrene-acrylic resin segment is addition-polymerized. (ii) A styrene-acrylic resin segment is prepared by addition polymerization of an addition-polymerizable monomer, and then a polyhydric alcohol and a polycarboxylic acid are condensation-polymerized. (iii) Polycondensation of a polyhydric alcohol and a polycarboxylic acid and addition polymerization of an addition-polymerizable monomer are carried out in parallel.
[0070] The proportion of the hybrid amorphous resin in the total binder resin is preferably 60% by mass or more and 98% by mass or less, more preferably 65% by mass or more and 95% by mass or less, and even more preferably 70% by mass or more and 90% by mass or less.
[0071] The characteristics of the amorphous resin will be described. The characteristics of the amorphous resin will be described.
[0072] The weight average molecular weight (Mw) of the amorphous resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.
[0073] The crystalline resin constituting the crystalline resin particles will be described. Examples of the crystalline resin include known crystalline resins such as crystalline polyester resins and crystalline vinyl resins (e.g., polyalkylene resins, long-chain alkyl (meth)acrylate resins, etc.) Among these, crystalline polyester resins are preferred from the viewpoints of the mechanical strength and low-temperature fixability of the toner.
[0074] Crystalline polyester resin The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. As the crystalline polyester resin, a commercially available product or a synthesized product may be used. Since the crystalline polyester resin easily forms a crystalline structure, a polycondensation product using a straight-chain aliphatic polymerizable monomer is preferable to a polymerizable monomer having an aromatic ring.
[0075] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower (e.g., carbon number 1 to 5) alkyl esters. As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0076] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0077] The polyhydric alcohol may have an aliphatic diol content of 80 mol % or more, and preferably 90 mol % or more.
[0078] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester resin.
[0079] As the crystalline polyester resin, a polymer of an α,ω-straight-chain aliphatic dicarboxylic acid and an α,ω-straight-chain aliphatic diol is preferable.
[0080] The α,ω-linear aliphatic dicarboxylic acid is preferably an α,ω-linear aliphatic dicarboxylic acid in which the alkylene group connecting the two carboxy groups has 3 or more and 14 or less carbon atoms, more preferably the alkylene group has 4 or more and 12 or less carbon atoms, and even more preferably the alkylene group has 6 or more and 10 or less carbon atoms. Examples of α,ω-linear aliphatic dicarboxylic acids include succinic acid, glutaric acid, adipic acid, 1,6-hexanedicarboxylic acid (commonly known as suberic acid), 1,7-heptanedicarboxylic acid (commonly known as azelaic acid), 1,8-octanedicarboxylic acid (commonly known as sebacic acid), 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid. Of these, 1,6-hexanedicarboxylic acid, 1,7-heptanedicarboxylic acid, 1,8-octanedicarboxylic acid, and 1,10-decanedicarboxylic acid are preferred. The α,ω-linear aliphatic dicarboxylic acids may be used alone or in combination of two or more kinds.
[0081] The α,ω-linear aliphatic diol is preferably an α,ω-linear aliphatic diol in which the alkylene group connecting the two hydroxy groups has 3 to 14 carbon atoms, more preferably the alkylene group has 4 to 12 carbon atoms, and further preferably the alkylene group has 6 to 10 carbon atoms. Examples of the α,ω-linear aliphatic diol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, and 1,18-octadecanediol. Of these, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred. The α,ω-linear aliphatic diols may be used alone or in combination of two or more kinds.
[0082] As the polymer of an α,ω-linear aliphatic dicarboxylic acid and an α,ω-linear aliphatic diol, from the viewpoint of suppressing image bleed, a polymer of at least one selected from the group consisting of 1,6-hexanedicarboxylic acid, 1,7-heptanedicarboxylic acid, 1,8-octanedicarboxylic acid, 1,9-nonanedicarboxylic acid, and 1,10-decanedicarboxylic acid and at least one selected from the group consisting of 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol is preferred, and among these, a polymer of 1,10-decanedicarboxylic acid and 1,6-hexanediol is more preferred.
[0083] The proportion of the crystalline polyester resin in the total binder resin is preferably from 1% by mass to 20% by mass, more preferably from 2% by mass to 15% by mass, and even more preferably from 3% by mass to 10% by mass. The characteristics of the crystalline resin will be described. The melting temperature of the crystalline resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."
[0084] The weight average molecular weight (Mw) of the crystalline resin is preferably 6,000 or more and 35,000 or less.
[0085] The dispersion medium used in the resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more kinds.
[0086] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.
[0087] In the resin particle dispersion, examples of the method for dispersing the resin particles in the dispersion medium include general dispersion methods using, for example, a rotary shear type homogenizer, a ball mill having a media, a sand mill, a dyno mill, etc. Depending on the type of resin particles, the resin particles may be dispersed in the resin particle dispersion using, for example, a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then an aqueous medium (W phase) is added to effect conversion of the resin from W / O to O / W (so-called phase inversion), resulting in a discontinuous phase, and the resin is dispersed in particulate form in the aqueous medium.
[0088] The content of the resin particles in the resin particle dispersion is, for example, preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.
[0089] -Colorant particle dispersion- The colorant particle dispersion is a dispersion in which a colorant is dispersed in at least an aqueous medium. Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, ultramarine blue, and tetrahydrofuran. Examples of the dyes include various pigments such as phosphorus blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate, and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.
[0090] The colorant is dispersed in the aqueous medium by a known method, and preferably used are, for example, a rotary shear homogenizer, a media type disperser such as a ball mill, a sand mill, an attritor, a high pressure counter collision type disperser, etc. The colorant may be dispersed in the aqueous medium using a homogenizer with a polar ionic surfactant to prepare a colorant particle dispersion.
[0091] The volume average particle size of the colorant is preferably 1 μm or less, more preferably 0.5 μm or less, and particularly preferably from 0.01 μm to 0.5 μm. Examples of dispersants that are added to further stabilize the dispersion stability of the colorant in an aqueous medium and to lower the energy of the colorant in the toner include rosin, rosin derivatives, coupling agents, and polymer dispersants.
[0092] Release agent particle dispersion The release agent particle dispersion is a dispersion in which a release agent is dispersed in at least an aqueous medium. Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these. The release agent may be used alone or in combination of two or more kinds. The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics."
[0093] The release agent is dispersed in an aqueous medium by a known method, and for example, a rotary shear type homogenizer, a media type dispersing machine such as a ball mill, a sand mill, an attritor, a high pressure counter collision type dispersing machine, etc. may be preferably used. The release agent may be dispersed in an aqueous solvent using a homogenizer with an ionic surfactant having polarity to prepare a release agent particle dispersion liquid. The volume average particle size of the release agent particles is preferably 1 μm or less, and more preferably 0.01 μm or more and 1 μm or more.
[0094] (1st agglomeration step) The first aggregation step will be described. In the first aggregation step, each particle is aggregated in a dispersion liquid containing first amorphous resin particles, crystalline resin particles, colorant particles, and release agent particles. For example, in the first aggregation step, first amorphous resin particles are mixed with a crystalline resin particle dispersion, a colorant particle dispersion, and a release agent particle dispersion, and the particles are aggregated in the resulting mixed dispersion. Then, in the mixed dispersion, the particles are hetero-aggregated to form primary aggregate particles containing the particles and having a diameter close to that of the target toner particles.
[0095] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature of the glass transition temperature of the resin particles (specifically, for example, a temperature of the glass transition temperature of the amorphous resin particles minus 30°C or more and the glass transition temperature minus 10°C or less), and the particles dispersed in the mixed dispersion are aggregated to form first aggregated particles. In the first aggregation step, for example, the mixed dispersion may be stirred with a rotary shear homogenizer while adding the above-mentioned aggregating agent at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to be acidic (e.g., pH 2 or more and 5 or less), and a dispersion stabilizer may be added as necessary, followed by the above-mentioned heating.
[0096] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant used as the dispersant added to the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. In particular, when a metal complex is used as the flocculant, the amount of surfactant used is reduced and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ions of the flocculant may be used, and a chelating agent is preferably used as this additive.
[0097] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate, as well as inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the amorphous resin particles.
[0098] -Second agglomeration process- In the second aggregation step, in a dispersion liquid containing first aggregated particles formed by aggregation of the first amorphous resin particles and second amorphous resin particles, the second amorphous resin particles are aggregated to the first aggregated particles. For example, in the second aggregation step, the first aggregated particle dispersion liquid and the second amorphous resin particle dispersion liquid are mixed, and the first aggregated particles are aggregated in the mixed dispersion liquid so that the second amorphous resin particles adhere to the surfaces of the first aggregated particles. Specifically, for example, in the first aggregation step, when the first aggregated particles reach a target particle size, a second amorphous resin particle dispersion is added to the first aggregated particle dispersion, and the dispersion is heated at a temperature equal to or lower than the glass transition temperature of the first and second amorphous resin particles. This aggregation operation is repeated one or more times to form the second aggregated particles.
[0099] Here, when the aggregation operation is repeated two or more times (i.e., when the second aggregation step is performed multiple times), in at least one aggregation operation excluding the last aggregation operation among the two or more aggregation operations, the second amorphous resin particle dispersion and the release agent particle dispersion are added to the first aggregated particle dispersion, and this dispersion is heated at a temperature equal to or lower than the glass transition temperature of the first and second amorphous resin particles. Here, the second amorphous resin particle dispersion and the release agent particle dispersion may be mixed in advance.
[0100] After the above aggregation operation is completed and the second aggregated particles reach a target particle size, the pH of the dispersion is adjusted to stop the progress of aggregation.
[0101] -Fusion process- In the fusion / coalescence step, the dispersion liquid containing the second aggregated particles is heated to fuse and coalesce the second aggregated particles to form toner particles. For example, in the fusion and coalescence process, the dispersion liquid containing the second aggregated particles is heated to a temperature equal to or higher than the glass transition temperature of the first and second amorphous resin particles (for example, a temperature 10 to 30°C higher than the glass transition temperature of the first and second amorphous resin particles) to fuse and coalesce the second aggregated particles to form toner particles.
[0102] After the fusion and coalescence process, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain toner particles in a dried state. In the washing step, it is preferable to carry out sufficient replacement washing with ion-exchanged water from the viewpoint of electrostatic charge. In addition, the solid-liquid separation step is not particularly limited, but it is preferable to carry out suction filtration, pressure filtration, etc. from the viewpoint of productivity. In addition, in the drying step, there is no particular limit to the method, but it is preferable to carry out freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc. from the viewpoint of productivity.
[0103] Then, for example, an external additive is added to the obtained dry toner particles and mixed to produce the toner. The mixing can be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner can be removed using a vibration sieve, an air sieve, etc.
[0104] Here, examples of the external additive include inorganic particles, such as SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2)n, Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, and MgSO4.
[0105] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the inorganic particles.
[0106] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate (PMMA), and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles).
[0107] The amount of the external additive added is, for example, preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.
[0108] (Characteristics of toner particles, etc.) The characteristics of the toner particles obtained by the toner production method according to this embodiment are as follows.
[0109] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 15 μm, and more preferably from 4 μm to 8 μm.
[0110] The various average particle sizes and particle size distribution indexes of the toner particles are measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5% aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. Based on the measured particle size distribution, cumulative distributions of volume and number are drawn for each divided particle size range (channel) from the smallest diameter side, and the particle size at 16% of the cumulative size is defined as the volume particle size D16v, the number particle size D16p, the particle size at 50% of the cumulative size as the volume average particle size D50v, the cumulative number average particle size D50p, and the particle size at 84% of the cumulative size as the volume particle size D84v and number particle size D84p. Using these, the volumetric particle size distribution index (GSDv) is (D84v / D16v) 1 / 2 The number size distribution index (GSDp) is (D84p / D16p) 1 / 2 It is calculated as:
[0111] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less.
[0112] The average circularity of toner particles is calculated by (circular equivalent perimeter) / (perimeter) [(perimeter of a circle having the same projected area as the particle image) / (perimeter of the particle projected image)]. Specifically, it is a value measured by the following method. First, the toner particles to be measured are sucked and collected, flattened, and a still image of the particles is captured by instantaneous strobe light emission, and the particle image is analyzed by a flow-type particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation). The number of samples to be taken in order to calculate the average circularity is 3,500. When the toner contains an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant, and then ultrasonic treatment is performed to obtain toner particles from which the external additive has been removed.
[0113] <Electrostatic image developer> The electrostatic image developer according to this embodiment contains at least the toner according to this embodiment. The electrostatic image developer according to the present embodiment may be a one-component developer containing only the toner according to the present embodiment, or may be a two-component developer in which the toner is mixed with a carrier.
[0114] The carrier is not particularly limited, and may be any known carrier, such as a coated carrier in which the surface of a core material made of magnetic powder is coated with a coating resin, a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin, or a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin. The magnetic powder dispersion type carrier and the resin impregnated type carrier may be a carrier in which the constituent particles of the carrier are used as a core material and are coated with a coating resin.
[0115] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt, and magnetic oxides such as ferrite and magnetite.
[0116] Examples of the coating resin and matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin containing an organosiloxane bond or a modified product thereof, fluororesin, polyester, polycarbonate, phenolic resin, and epoxy resin. The coating resin and the matrix resin may contain other additives such as conductive particles. Examples of the conductive particles include particles of metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.
[0117] Here, in order to coat the surface of the core material with a coating resin, a method of coating with a coating layer forming solution in which the coating resin and, if necessary, various additives are dissolved in an appropriate solvent can be mentioned. The solvent is not particularly limited and may be selected taking into consideration the coating resin to be used, the suitability for application, etc. Specific resin coating methods include an immersion method in which the core material is immersed in a solution for forming a coating layer, a spray method in which the solution for forming a coating layer is sprayed onto the surface of the core material, a fluidized bed method in which the solution for forming a coating layer is sprayed onto the core material while it is suspended in flowing air, and a kneader coater method in which the core material of a carrier and the solution for forming a coating layer are mixed in a kneader coater and the solvent is removed.
[0118] In the two-component developer, the mixture ratio (mass ratio) of the toner and the carrier is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.
[0119] <Image forming device / image forming method> An image forming apparatus / image forming method according to this embodiment will be described. The image forming apparatus according to the present embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image carrier, a developing means for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image with the electrostatic image developer, a transfer means for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing means for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to the present embodiment is used as the electrostatic image developer.
[0120] In the image forming apparatus according to this embodiment, an image forming method (the image forming method according to this embodiment) is carried out, which includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.
[0121] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as a direct transfer type apparatus in which a toner image formed on the surface of an image holder is directly transferred to a recording medium; an intermediate transfer type apparatus in which a toner image formed on the surface of an image holder is primarily transferred to the surface of an intermediate transfer body, and the toner image transferred to the surface of the intermediate transfer body is then secondarily transferred to the surface of a recording medium; an apparatus equipped with a cleaning means for cleaning the surface of the image holder before charging after the transfer of the toner image; and an apparatus equipped with a discharging means for irradiating the surface of the image holder with discharging light to discharge it before charging after the transfer of the toner image. In the case of an intermediate transfer type device, the transfer means has, for example, an intermediate transfer body onto whose surface a toner image is transferred, a primary transfer means which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer means which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.
[0122] In the image forming apparatus according to the present embodiment, for example, a portion including the developing means may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge including a developing means that contains the electrostatic image developer according to the present embodiment is preferably used.
[0123] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.
[0124] FIG. 1 is a schematic diagram showing the configuration of an image forming apparatus according to the present embodiment. The image forming apparatus shown in Fig. 1 includes first to fourth electrophotographic image forming units 10Y, 10M, 10C, and 10K (image forming means) that output images of each color of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachable from the image forming apparatus.
[0125] Above each of the units 10Y, 10M, 10C, and 10K in the drawing, an intermediate transfer belt 20 is provided as an intermediate transfer body extending through each unit. The intermediate transfer belt 20 is provided wound around a drive roll 22 and a support roll 24 that are arranged from left to right in the drawing at a distance from each other and contact the inner surface of the intermediate transfer belt 20, and is adapted to run in a direction from the first unit 10Y to the fourth unit 10K. Note that a force is applied to the support roll 24 in a direction away from the drive roll 22 by a spring or the like (not shown), and tension is applied to the intermediate transfer belt 20 wound around them. In addition, an intermediate transfer body cleaning device 30 is provided on the image carrier side of the intermediate transfer belt 20, facing the drive roll 22. Further, the developing devices (developing means) 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with toner including four colors of toner, yellow, magenta, cyan, and black, contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.
[0126] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative example. Note that by assigning reference numerals of magenta (M), cyan (C), and black (K) instead of yellow (Y) to parts equivalent to those of the first unit 10Y, descriptions of the second to fourth units 10M, 10C, and 10K will be omitted.
[0127] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging means) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming means) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device (an example of a developing means) 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll 5Y (an example of a primary transfer means) that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning means) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order. The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20 and is provided at a position facing the photoconductor 1Y. Furthermore, a bias power supply (not shown) that applies a primary transfer bias is connected to each of the primary transfer rolls 5Y, 5M, 5C, and 5K. Each bias power supply varies the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).
[0128] Hereinafter, the operation of forming a yellow image in the first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity at 20° C. of 1×10 -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam 3Y, the resistivity of the portion irradiated with the laser beam changes. A laser beam 3Y is output to the charged surface of the photoreceptor 1Y via an exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). The laser beam 3Y is irradiated onto the photosensitive layer on the surface of the photoreceptor 1Y, and an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.
[0129] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y is rotated to a predetermined developing position as the photoconductor 1Y travels. Then, at this developing position, the electrostatic image on the photoconductor 1Y is made visible as a toner image (developed image) by the developing device 4Y.
[0130] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.
[0131] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and in the first unit 10Y, for example, it is controlled to +10 μA by a control unit (not shown). On the other hand, the toner remaining on the photoconductor 1Y is removed and collected by the photoconductor cleaning device 6Y.
[0132] Further, the primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K subsequent to the second unit 10M is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of the respective colors are transferred in a superimposed manner.
[0133] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer means) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.
[0134] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in a fixing device (one example of a fixing means) 28, where the toner image is fixed onto the recording paper P, forming a fixed image.
[0135] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets, etc. To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, coated paper in which the surface of ordinary paper is coated with resin or the like, art paper for printing, etc. are preferably used.
[0136] After the color image has been fixed, the recording paper P is conveyed toward the discharge section, and the series of color image forming operations is completed.
[0137] <Process cartridge / toner cartridge> The process cartridge according to this embodiment will be described. The process cartridge according to this embodiment is a process cartridge that contains the electrostatic image developer according to this embodiment, is equipped with a developing means that develops an electrostatic image formed on the surface of an image carrier using the electrostatic image developer into a toner image, and is detachably attached to an image forming apparatus.
[0138] In addition, the process cartridge according to this embodiment is not limited to the above configuration, and may be configured to include a developing device and, as necessary, at least one other means selected from an image carrier, a charging means, an electrostatic image forming means, and a transfer means.
[0139] An example of a process cartridge according to the present embodiment will be described below, but the present invention is not limited to this example. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.
[0140] FIG. 2 is a schematic diagram showing the process cartridge according to the present embodiment. The process cartridge 200 shown in FIG. 2 is configured by, for example, a housing 117 having a mounting rail 116 and an opening 118 for exposure, and integrally combining and holding a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging means) provided around the photoconductor 107, a developing device 111 (an example of a developing means), and a photoconductor cleaning device 113 (an example of a cleaning means), which are assembled into a cartridge. In FIG. 2, 109 denotes an exposure device (an example of an electrostatic image forming means), 112 denotes a transfer device (an example of a transfer means), 115 denotes a fixing device (an example of a fixing means), and 300 denotes recording paper (an example of a recording medium).
[0141] Next, the toner cartridge according to this embodiment will be described. The toner cartridge according to the present embodiment is a toner cartridge that contains the toner according to the present embodiment and is detachably attached to an image forming apparatus. The toner cartridge contains replenishment toner to be supplied to a developing unit provided in the image forming apparatus.
[0142] 1 is an image forming apparatus having a configuration in which toner cartridges 8Y, 8M, 8C, and 8K can be attached and detached, and the developing devices 4Y, 4M, 4C, and 4K are connected to the toner cartridges corresponding to the respective developing devices (colors) through toner supply pipes (not shown). When the toner contained in the toner cartridge becomes low, the toner cartridge is replaced. EXAMPLES
[0143] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" are by mass. Synthesis, processing, preparation, etc. were carried out at room temperature (25°C ± 3°C) unless otherwise noted.
[0144] <Preparation of particle dispersion> [Preparation of amorphous polyester resin particle dispersion (A1)] Terephthalic acid: 69 parts Fumaric acid: 31 parts Ethylene glycol: 40 parts 1,5-Pentanediol: 45 parts The above materials were placed in a reaction tank equipped with a stirrer, nitrogen inlet tube, temperature sensor, and distillation column, and the temperature was raised to 220°C over 1 hour under nitrogen gas flow, and 1 part of titanium tetraethoxide was added for a total of 100 parts of the above materials. The temperature was raised to 240°C over 0.5 hours while distilling off the generated water, and the dehydration condensation reaction was continued at 240°C for 1 hour, after which the reaction product was cooled. In this way, an amorphous polyester resin (A) with a weight average molecular weight of 96,000 and a glass transition temperature of 59°C was obtained.
[0145] In a tank equipped with a temperature control means and a nitrogen substitution means, 53 parts of ethyl acetate and 25 parts of 2-butanol were added to prepare a mixed solvent, and then 100 parts of amorphous polyester resin (A) were gradually added and dissolved, and 10% aqueous ammonia solution (equivalent to 3 times the amount by molar ratio relative to the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the reaction vessel was substituted with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped into the mixed liquid while stirring, to perform emulsification. After the dropwise addition, the emulsion was returned to 25°C, and the solvent was removed under reduced pressure to obtain a resin particle dispersion in which resin particles with a volume average particle size of 170 nm were dispersed. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, and an amorphous polyester resin particle dispersion (A1) was obtained.
[0146] [Preparation of amorphous polyester resin particle dispersion (A2)] Using the amorphous polyester resin (A), the amorphous polyester resin particle dispersion (A2) having a volume average particle size of 70 nm and a solid content of 20% was obtained in the same manner as in the preparation of the amorphous polyester resin particle dispersion (A1), except that 53 parts of ethyl acetate was changed to 80 parts of ethyl acetate.
[0147] [Preparation of amorphous polyester resin particle dispersion (A3)] Using the amorphous polyester resin (A), the amorphous polyester resin particle dispersion (A3) having a volume average particle size of 220 nm and a solid content of 20% was obtained in the same manner as in the preparation of the amorphous polyester resin particle dispersion (A1), except that 53 parts of ethyl acetate was changed to 47 parts of ethyl acetate.
[0148] [Preparation of amorphous polyester resin particle dispersion (A4)] Using the amorphous polyester resin (A), the preparation of the amorphous polyester resin particle dispersion (A1) was carried out in the same manner as above, except that 53 parts of ethyl acetate was changed to 64 parts of ethyl acetate, to obtain an amorphous polyester resin particle dispersion (A4) having a volume average particle size of 130 nm and a solid content of 20%.
[0149] [Preparation of amorphous polyester resin particle dispersion (A5)] Using the amorphous polyester resin (A), the preparation of the amorphous polyester resin particle dispersion (A1) was carried out in the same manner as above, except that 53 parts of ethyl acetate was changed to 58 parts of ethyl acetate, to obtain an amorphous polyester resin particle dispersion (A5) having a volume average particle size of 150 nm and a solid content of 20%.
[0150] [Preparation of amorphous polyester resin particle dispersion (A6)] Using the amorphous polyester resin (A), the preparation of the amorphous polyester resin particle dispersion (A1) was carried out in the same manner as above, except that 53 parts of ethyl acetate was changed to 75 parts of ethyl acetate, to obtain an amorphous polyester resin particle dispersion (A6) having a volume average particle size of 80 nm and a solid content of 20%.
[0151] [Preparation of amorphous polyester resin particle dispersion (A7)] Using the amorphous polyester resin (A), the preparation of the amorphous polyester resin particle dispersion (A1) was carried out in the same manner as above, except that 53 parts of ethyl acetate was changed to 66 parts of ethyl acetate, to obtain an amorphous polyester resin particle dispersion (A7) having a volume average particle size of 100 nm and a solid content of 20%.
[0152] [Preparation of amorphous polyester resin particle dispersion (A8)] Amorphous polyester resin (A) was used in the same manner as in the preparation of amorphous polyester resin particle dispersion (A1), except that 53 parts of ethyl acetate was changed to 68 parts of ethyl acetate, to obtain amorphous polyester resin particle dispersion (A8) having a volume average particle size of 90 nm and a solid content of 20%.
[0153] [Preparation of amorphous polyester resin particle dispersion (A9)] Using the amorphous polyester resin (A), the amorphous polyester resin particle dispersion (A9) having a volume average particle size of 50 nm and a solid content of 20% was obtained in the same manner as in the preparation of the amorphous polyester resin particle dispersion (A1), except that 53 parts of ethyl acetate was changed to 85 parts of ethyl acetate.
[0154] [Preparation of amorphous polyester resin particle dispersion (A10)] Using the amorphous polyester resin (A), the amorphous polyester resin particle dispersion (A10) having a volume average particle size of 300 nm and a solid content of 20% was obtained in the same manner as in the preparation of the amorphous polyester resin particle dispersion (A1), except that 53 parts of ethyl acetate was changed to 40 parts of ethyl acetate.
[0155] [Preparation of amorphous polyester resin particle dispersion (A11)] Using the amorphous polyester resin (A), the amorphous polyester resin particle dispersion (A11) having a volume average particle size of 320 nm and a solid content of 20% was obtained in the same manner as in the preparation of the amorphous polyester resin particle dispersion (A1), except that 53 parts of ethyl acetate was changed to 39 parts of ethyl acetate.
[0156] [Preparation of amorphous polyester resin particle dispersion (A12)] Using the amorphous polyester resin (A), the amorphous polyester resin particle dispersion (A12) having a volume average particle size of 12 nm and a solid content of 20% was obtained in the same manner as in the preparation of the amorphous polyester resin particle dispersion (A1), except that 53 parts of ethyl acetate was changed to 105 parts of ethyl acetate.
[0157] [Preparation of amorphous polyester resin particle dispersion (A13)] Using the amorphous polyester resin (A), the amorphous polyester resin particle dispersion (A13) having a volume average particle size of 30 nm and a solid content of 20% was obtained in the same manner as in the preparation of the amorphous polyester resin particle dispersion (A1), except that 53 parts of ethyl acetate was changed to 90 parts of ethyl acetate.
[0158] [Preparation of amorphous polyester resin particle dispersion (A14)] Using the amorphous polyester resin (A), the amorphous polyester resin particle dispersion (A14) having a volume average particle size of 180 nm and a solid content of 20% was obtained in the same manner as in the preparation of the amorphous polyester resin particle dispersion (A1), except that 53 parts of ethyl acetate was changed to 51 parts of ethyl acetate.
[0159] [Preparation of amorphous polyester resin particle dispersion (B1)] Terephthalic acid: 69 parts Fumaric acid: 31 parts Ethylene glycol: 40 parts 1,5-Pentanediol: 45 parts The above materials were placed in a reaction vessel equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column, and the temperature was raised to 220°C over 0.8 hours under a nitrogen gas stream, and 1.1 parts of titanium tetraethoxide was added per 100 parts of the above materials in total. The temperature was raised to 240°C over 0.4 hours while distilling off the water produced, and the dehydration condensation reaction was continued at 240°C for 0.9 hours, after which the reaction product was cooled. In this way, an amorphous polyester resin (B1) with a weight average molecular weight of 96,000 and a glass transition temperature of 50°C was obtained.
[0160] In a tank equipped with a temperature control means and a nitrogen substitution means, 52 parts of ethyl acetate and 25 parts of 2-butanol were added to prepare a mixed solvent, and then 100 parts of amorphous polyester resin (B1) were gradually added and dissolved, and 10% aqueous ammonia solution (equivalent to 3 times the amount by molar ratio relative to the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the reaction vessel was substituted with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped into the mixed liquid while stirring, to perform emulsification. After the dropwise addition, the emulsion was returned to 25°C, and the solvent was removed under reduced pressure to obtain a resin particle dispersion in which resin particles with a volume average particle size of 175 nm were dispersed. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, and an amorphous polyester resin particle dispersion (B1) was obtained.
[0161] [Preparation of amorphous polyester resin particle dispersion (B2)] In a tank equipped with a temperature control means and a nitrogen substitution means, 53 parts of ethyl acetate and 25 parts of 2-butanol were added to prepare a mixed solvent, and then 100 parts of amorphous polyester resin (B1) were gradually added and dissolved, and 10% aqueous ammonia solution (equivalent to 3 times the amount by molar ratio relative to the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the reaction vessel was substituted with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped into the mixed liquid while stirring, to perform emulsification. After the dropwise addition, the emulsion was returned to 25°C, and the solvent was removed under reduced pressure to obtain a resin particle dispersion in which resin particles with a volume average particle size of 170 nm were dispersed. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, and an amorphous polyester resin particle dispersion (B2) was obtained.
[0162] [Preparation of amorphous polyester resin particle dispersion (B3)] Terephthalic acid: 69 parts Fumaric acid: 31 parts Ethylene glycol: 40 parts 1,5-Pentanediol: 45 parts The above materials were placed in a reaction vessel equipped with a stirrer, nitrogen inlet tube, temperature sensor and distillation column, and the temperature was raised to 220°C over 1.3 hours under nitrogen gas flow, and 0.9 parts of titanium tetraethoxide was added per 100 parts of the above materials. The temperature was raised to 240°C over 0.6 hours while distilling off the water produced, and the dehydration condensation reaction was continued at 240°C for 1.2 hours, after which the reaction product was cooled. In this way, an amorphous polyester resin (B3) with a weight average molecular weight of 96,000 and a glass transition temperature of 63°C was obtained.
[0163] In a tank equipped with a temperature control means and a nitrogen substitution means, 53 parts of ethyl acetate and 25 parts of 2-butanol were added to prepare a mixed solvent, and then 100 parts of amorphous polyester resin (B3) were gradually added and dissolved, and 10% aqueous ammonia solution (equivalent to 3 times the amount by molar ratio relative to the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the reaction vessel was substituted with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped into the mixed liquid while stirring, to perform emulsification. After the dropwise addition, the emulsion was returned to 25°C, and the solvent was removed under reduced pressure to obtain a resin particle dispersion in which resin particles with a volume average particle size of 170 nm were dispersed. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, and an amorphous polyester resin particle dispersion (B3) was obtained.
[0164] [Preparation of amorphous polyester resin particle dispersion (B4)] Terephthalic acid: 69 parts Fumaric acid: 31 parts Ethylene glycol: 40 parts 1,5-Pentanediol: 45 parts The above materials were placed in a reaction tank equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column, and the temperature was raised to 225°C over 0.6 hours under a nitrogen gas flow, and 1.1 parts of titanium tetraethoxide was added per 100 parts of the above materials. The temperature was raised to 245°C over 0.3 hours while distilling off the water produced, and the dehydration condensation reaction was continued at 245°C for 0.9 hours, after which the reaction product was cooled. In this way, an amorphous polyester resin (B4) with a weight average molecular weight of 96,000 and a glass transition temperature of 45°C was obtained.
[0165] In a tank equipped with a temperature control means and a nitrogen substitution means, 52 parts of ethyl acetate and 25 parts of 2-butanol were added to prepare a mixed solvent, and then 100 parts of amorphous polyester resin (B4) were gradually added and dissolved, and 10% aqueous ammonia solution (equivalent to 3 times the amount by molar ratio relative to the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the reaction vessel was substituted with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped into the mixed liquid while stirring, to perform emulsification. After the dropwise addition, the emulsion was returned to 25°C, and the solvent was removed under reduced pressure to obtain a resin particle dispersion in which resin particles with a volume average particle size of 175 nm were dispersed. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, and an amorphous polyester resin particle dispersion (B4) was obtained.
[0166] [Preparation of amorphous polyester resin particle dispersion (B5)] In a tank equipped with a temperature control means and a nitrogen substitution means, 53 parts of ethyl acetate and 25 parts of 2-butanol were added to prepare a mixed solvent, and then 100 parts of amorphous polyester resin (B4) were gradually added and dissolved, and 10% aqueous ammonia solution (equivalent to 3 times the amount by molar ratio relative to the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the reaction vessel was substituted with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped into the mixed liquid while stirring, to perform emulsification. After the dropwise addition, the emulsion was returned to 25°C, and the solvent was removed under reduced pressure to obtain a resin particle dispersion in which resin particles with a volume average particle size of 170 nm were dispersed. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, and an amorphous polyester resin particle dispersion (B5) was obtained.
[0167] [Preparation of amorphous polyester resin particle dispersion (B6)] Terephthalic acid: 69 parts Fumaric acid: 31 parts Ethylene glycol: 40 parts 1,5-Pentanediol: 45 parts The above materials were placed in a reaction vessel equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column, and the temperature was raised to 220°C over 1.5 hours under a nitrogen gas stream, and 0.8 parts of titanium tetraethoxide was added per 100 parts of the above materials. The temperature was raised to 240°C over 0.8 hours while distilling off the water produced, and the dehydration condensation reaction was continued at 240°C for 1.2 hours, after which the reaction product was cooled. In this way, an amorphous polyester resin (B6) with a weight average molecular weight of 96,000 and a glass transition temperature of 67°C was obtained.
[0168] In a tank equipped with a temperature control means and a nitrogen substitution means, 53 parts of ethyl acetate and 25 parts of 2-butanol were added to prepare a mixed solvent, and then 100 parts of amorphous polyester resin (B6) were gradually added and dissolved, and 10% aqueous ammonia solution (equivalent to 3 times the amount by molar ratio relative to the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the reaction vessel was substituted with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped into the mixed liquid while stirring, to perform emulsification. After the dropwise addition, the emulsion was returned to 25°C, and the solvent was removed under reduced pressure to obtain a resin particle dispersion in which resin particles with a volume average particle size of 170 nm were dispersed. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, and an amorphous polyester resin particle dispersion (B3) was obtained.
[0169] [Preparation of crystalline polyester resin particle dispersion (C)] 1,10-Decanedicarboxylic acid: 260 parts 1,6-Hexanediol: 167 parts Dibutyltin oxide (catalyst): 0.3 parts The above materials were placed in a heated and dried reactor, the air in the reactor was replaced with nitrogen gas to create an inert atmosphere, and the mixture was stirred and refluxed at 180°C for 5 hours using mechanical stirring. The temperature was then gradually increased to 230°C under reduced pressure and the mixture was stirred for 2 hours, and when the mixture became viscous, it was air-cooled to stop the reaction. Thus, a crystalline polyester resin with a weight average molecular weight of 12600 and a melting temperature of 73°C was obtained. 90 parts of crystalline polyester resin, 1.8 parts of anionic surfactant (TaycaPower, manufactured by Tayca Corporation) and 210 parts of ion-exchanged water were mixed, heated to 120°C, dispersed using a homogenizer (Ultra Turrax T50 manufactured by IKA Corporation), and then dispersed for 1 hour using a pressure discharge type Gaulin homogenizer to obtain a resin particle dispersion in which resin particles with a volume average particle size of 160 nm were dispersed. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20%, and a crystalline polyester resin particle dispersion (C) was obtained.
[0170] [Preparation of release agent particle dispersion (W1)] Paraffin wax (manufactured by Nippon Seiro Co., Ltd., FNP92, melting temperature 92°C): 100 parts Anionic surfactant (TaycaPower, manufactured by Tayca Corporation): 1 part Ion-exchanged water: 350 parts The above materials were mixed and heated to 100°C, dispersed using a homogenizer (IKA Ultra Turrax T50), and then dispersed using a pressure discharge Gaulin homogenizer to obtain a release agent particle dispersion in which release agent particles with a volume average particle size of 220 nm were dispersed. Ion-exchanged water was added to this release agent particle dispersion to adjust the solid content to 20%, and this was used as release agent particle dispersion (W1).
[0171] [Preparation of colorant particle dispersion (K)] Carbon black (Cabot, Regal 330): 50 parts Anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts Ion-exchanged water: 193 parts The above materials were mixed and dispersed for 10 minutes at 240 MPa using an Ultimizer (manufactured by Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (K) with a solid content concentration of 20%.
[0172] <Example 1> [First agglomeration step] Ion-exchanged water: 500 parts Amorphous polyester resin particle dispersion (A1): 530 parts Crystalline polyester resin particle dispersion (C): 150 parts Release agent particle dispersion (W1): 150 parts Colorant particle dispersion (K): 150 parts The above materials were placed in a reaction vessel as feedstock, and the pH was adjusted to 3.5 by adding 0.1N nitric acid. An aqueous solution of aluminum sulfate prepared by dissolving 1.5 parts of aluminum sulfate in 100 parts of ion-exchanged water was charged into the reaction tank. The mixture was dispersed at a liquid temperature of 30° C. using a homogenizer (IKA Ultra Turrax T50), then heated to a liquid temperature of 45° C. in a heating oil bath and maintained at this temperature until the volume average particle size of the aggregated particles reached 4.0 μm.
[0173] [Second agglomeration process] To the dispersion containing the aggregated particles, 90 parts of the amorphous polyester resin particle dispersion (A2) and 30 parts of the release agent particle dispersion (W1) were added as additional dispersions, and the mixture was maintained for 30 minutes. Thereafter, 115 parts of the amorphous polyester resin particle dispersion (A2) was added as an additional dispersion to the dispersion containing the aggregated particles, and the mixture was maintained for 30 minutes. The pH was then adjusted to 9.0 with 1N aqueous sodium hydroxide solution.
[0174] [Fusion process] While continuing stirring in the reaction tank, the temperature was increased to 85°C at a rate of 0.5°C / min, and the mixture was maintained at 85°C for 3 hours, and then cooled to 30°C at a rate of 15°C / min (first cooling). Next, the mixture was heated to 55°C at a rate of 0.2°C / min (reheating), maintained for 30 minutes, and then cooled to 30°C at a rate of 0.5°C / min (second cooling). Next, the solid content was filtered, washed with ion-exchanged water, and dried to obtain toner particles (K1) having a volume average particle size of 5.0 μm.
[0175] [Addition of external additives] 100 parts of toner particles (K1) and 1.5 parts of hydrophobic silica (RY50, manufactured by Nippon Aerosil Co., Ltd.) were mixed and mixed for 30 seconds at a rotation speed of 10,000 rpm using a sample mill. The mixture was sieved using a vibrating sieve with an opening of 45 μm to obtain toner (K1). The volume average particle diameter of toner (K1) was 5.0 μm.
[0176] [Creating the carrier] After 500 parts of spherical magnetite powder particles (volume average particle diameter 0.55 μm) were stirred with a Henschel mixer, 5 parts of a titanate-based coupling agent were added, and the mixture was heated to 100 ° C and stirred for 30 minutes. Next, 6.25 parts of phenol, 9.25 parts of 35% formalin, 500 parts of magnetite particles treated with a titanate-based coupling agent, 6.25 parts of 25% ammonia water, and 425 parts of water were added to a four-neck flask and stirred, and reacted at 85 ° C for 120 minutes while stirring. Next, the mixture was cooled to 25 ° C, 500 parts of water were added, and the supernatant liquid was removed and the precipitate was washed with water. The washed precipitate was heated and dried under reduced pressure to obtain a carrier (CA) with an average particle size of 35 μm.
[0177] [Preparation of developer] The toner (K1) and the carrier (CA) were placed in a V blender in a ratio of toner (K1):carrier (CA)=5:95 (mass ratio) and stirred for 20 minutes to obtain a developer (K1).
[0178] <Examples 2 to 17 and Comparative Examples 1 to 7> Toner particles were obtained in the same manner as in Example 1, except that the specifications were changed as shown in Table 1. Next, in the same manner as in Example 1, external additives were added to the toner particles, and mixed with a carrier to obtain a developer.
[0179] <Evaluation> (Solid content concentration of dispersion during the first aggregation step) In the first flocculation step, the solid concentration of the dispersion liquid at the time of dispersion using a homogenizer was measured using a moisture content meter ("HB43-S" manufactured by Mettler Toledo Co., Ltd.).
[0180] (Toner particle size distribution (GSD), release agent exposure rate) The obtained toner particles were measured for the volume particle size distribution index (GSDv=(D84v / D16v)) according to the method described above. 1 / 2 ) and the exposure rate of the release agent was measured. However, the exposure rate of the release agent was evaluated according to the following criteria. A: The exposure rate of the release agent is less than 15%. B: Release agent exposure rate is 15% or more but less than 20% C: Release agent exposure rate is 20% or more but less than 25% D: Release agent exposure rate is 25% or more but less than 100%
[0181] [Table 1-1]
[0182] [Table 1-2]
[0183] From the above results, it is understood that in this embodiment, a toner having a narrower particle size distribution can be obtained compared to the comparative example. [Explanation of symbols]
[0184] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (an example of a charging means) 3 Exposure device (an example of an electrostatic image forming means) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device (an example of developing means) 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6Y, 6M, 6C, 6K Photoconductor cleaning device (an example of a cleaning means) 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer means) 28 Fixing device (an example of a fixing means) 30 Intermediate transfer body cleaning device P Recording paper (an example of a recording medium) 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of charging means) 109 Exposure device (an example of electrostatic image forming means) 111 Developing device (an example of developing means) 112 Transfer device (an example of a transfer means) 113 Photoconductor cleaning device (an example of a cleaning means) 115 Fixing device (an example of fixing means) 116 Mounting Rail 117 Cabinet 118 Exposure Aperture 200 Process Cartridge 300 Recording paper (an example of a recording medium)
Claims
1. a first aggregation step of aggregating at least the first amorphous resin particles in a dispersion liquid containing the first amorphous resin particles; a second aggregation step of aggregating the second amorphous resin particles to the first aggregated particles in a dispersion liquid containing first aggregated particles formed by aggregating the first amorphous resin particles and second amorphous resin particles; a fusion / coalescence process of heating a dispersion liquid containing second aggregate particles in which the second amorphous resin particles are aggregated to the first aggregate particles, to fuse and coalesce the second aggregate particles to form toner particles; having The volume average particle diameter D of the second amorphous resin particles is smaller than the volume average particle diameter D of the first amorphous resin particles, The first amorphous resin particles have a glass transition temperature of 50° C. or more, and the second amorphous resin particles have a glass transition temperature of 50° C. or more and 63° C. or less; The second aggregation step is carried out a plurality of times; and at least one of the second aggregation steps, except for the last one, is a step of adding a dispersion liquid in which the second amorphous resin particles are dispersed and a dispersion liquid in which release agent particles are dispersed to a dispersion liquid in which the first aggregated particles are dispersed, or adding a dispersion liquid in which the dispersion liquid in which the second amorphous resin particles are dispersed and a dispersion liquid in which the release agent particles are dispersed in advance to a dispersion liquid containing the first aggregated particles, the second amorphous resin particles, and the release agent particles to be aggregated together with the second amorphous resin particles to the first aggregated particles in the dispersion liquid containing the first aggregated particles, the second amorphous resin particles, and the release agent particles. A method for producing a toner for developing electrostatic images.
2. 2. The method for producing a toner for developing an electrostatic image according to claim 1, wherein an exposure rate of the release agent on the surface of the obtained toner particles is 25% or less.
3. 3. The method for producing a toner for developing an electrostatic image according to claim 1, wherein a difference (DA-DB) between a volume average particle diameter DA of the first amorphous resin particles and a volume average particle diameter DB of the second amorphous resin particles is 20 nm or more.
4. 4. The method for producing a toner for developing an electrostatic image according to claim 3, wherein a difference (DA-DB) between a volume average particle diameter DA of the first amorphous resin particles and a volume average particle diameter DB of the second amorphous resin particles is 20 nm or more and 300 nm or less.
5. The first amorphous resin particles have a volume average particle size (DA) of 100 nm or more and 300 nm or less, 5. The method for producing a toner for developing an electrostatic image according to claim 1, wherein the second amorphous resin particles have a volume average particle diameter DB of 20 nm or more and 170 nm or less.
6. the second amorphous resin particles include two or more types of amorphous resin particles having different volume average particle diameters, 6. The method for producing a toner for developing electrostatic images according to claim 5, wherein the volume average particle diameter of the mixed particles obtained by mixing the two or more kinds of amorphous resin particles having different volume average particle diameters is in the range of 20 nm to 170 nm, which is the range of the volume average particle diameter DB of the second amorphous resin particles.
7. 7. The method for producing a toner for developing electrostatic images according to claim 1, wherein a ratio of particles having a particle size of 100 nm or less in a particle size distribution of the second amorphous resin particles is 10 volume % or more and 100 volume % or less.
Citation Information
Patent Citations
Electrostatic charge image developing toner
JP2005221933A
Toner for electrostatic charge image development, method for manufacturing the same, electrostatic charge image developer, and image forming method
JP2007003840A
Functional particle and method for producing the same
JP2008065180A
Toner for electrostatic charge image development, manufacturing method thereof, and image forming apparatus
JP2009151060A
Electrostatic charge image developing toner, electrostatic charge image developer and image forming method
JP2009300848A